(untitled) (Open Academia: Journal of Scholarly Research, 2024)
patients with Covid-19 (SARS-CoV-2) have experienced a lot of psychoemotional disorders and put people in depression. The power of my organism to fight the disease was studied in a psychological state. The disease was analyzed by the Fergana region, depending on gender, age, initial clinical signs.